Effect of playing tactics on goal scoring in Norwegian professional soccer - Tenga, A.; Holme, I.; Ronglan, L. T.; Bahr, R. (Journal of Sports Sciences, 2010)
Methods that include an assessment of opponent interactions are thought to provide a more valid analysis of team match performance. The purpose of this study was to examine the effect of playing tactics on goal scoring by assessing opponent interactions in Norwegian elite soccer. The sample included 203 team possessions leading to goals (cases) and 1688 random team possessions (control group) from 163 of 182 (90%) matches played in the men's professional league during the 2004 season. Multidimensional qualitative data using ten ordered categorical variables were obtained to characterize each team possession. The proportion of goals scored during counterattacks (52%) was higher than during elaborate attacks (48%), while for the control group the proportion using elaborate attacks (59%) was higher than when using counterattacks (41%) (P = 0.002). Multiple logistic regression analyses showed that, for the main variable "team possession type", counterattacks were more effective than elaborate attacks when playing against an imbalanced defence (OR = 1.64; 95% confidence interval: 1.03 to 2.61; P = 0.038). Assessment of opponent interactions is critical to evaluate the effectiveness of offensive playing tactics on the probability of scoring goals, and improves the validity of team match-performance analysis in soccer.